'I Miss My Little One A Lot': How Father Love Motivates Change in Men Who Have Used Violence. (17th March 2015) - Broady, Timothy R.; Gray, Rebecca; Gaffney, Irene; Lewis, Pamela
Abstract : This paper presents selected findings from a research‐based evaluation of a men's domestic violence intervention programme, which aims to assist men to develop alternative ways of relating to their partners, children and others. The qualitative component of this evaluation involved conducting interviews with 21 group participants after their completion of the course. These interviews investigated several issues, including participants' perceptions of their relationships with their children. The main theme underpinning all discussions of children was an expression of love, in that love for their children served as a motivation to stop using violence and to develop alternative ways of relating to all family members. The paper concludes by discussing the potential of men's relationships with their children as powerful contexts, or points of leverage, through which the impact of their violent behaviour can be realised and confronted. By realising the impact that violent behaviour can have on children's wellbeing and fathers' interpersonal relationships with them, it is argued that intervention programmes can support men to develop more appropriate ways of relating to their children, and thus safeguard children from potential long‐term consequences of domestic abuse. Copyright © 2015 John Wiley & Sons, Ltd. 'The main theme underpinning all discussions of children was an expression of love' Key Practitioner Messages: Men attending domestic violence intervention programmes demonstrate a wide range of attitudes towards their partners and former partners, but unanimously report a desire to maintain meaningful relationships with their children. Men who have used violence in their family relationships can be challenged and motivated to change through realising the impact of their behaviour on their children's wellbeing and their father‐child relationships. 'Unanimously report a desire to maintain meaningful relationships with their children'